Generating Neural Stem Cells from iPSCs with Dopaminergic Neurons Reporter Gene - Hong, Hyenjong (Methods Mol Biol, 2019)
Genetic reporters offer attractive approaches to investigate gene expression, gene function, and spatiotemporal assessment in vitro and in vivo. Tyrosine hydroxylase (TH) is the rate-limiting enzyme for the biosynthesis of the dopamine neurotransmitter, and thus it has been used as a reliable marker for dopaminergic neurons in vitro and in vivo. Herein we describe a method for making iPSC lines with TH-green fluorescent protein reporter gene using CRISPR/Cas9 technique.